1996
DOI: 10.1007/bf00181662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thoracotomy and cardiopulmonary bypass on activated platelet and neutrophil dynamics and platelet emboli in a pig model

Abstract: The effects of thoracotomy and components of extracorporeal circuits on dynamics of platelets and neutrophils were quantified with autologous In-111-labeled platelets (INPLT) and neutrophils (INN) during cardiopulmonary bypass (CPB) operations in Yorkshire pigs. Cardiopulmonary bypass was carried out with a hollow-fiber oxygenator and an arterial filter in 48 pigs (30-35 kg; 12 unoperated controls for platelets and neutrophils; 12 sham operated controls; 12 with 180 minutes of CPB with platelets and neutrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In this study, we did not find any differences between SMA and standard CPB circuits in the total or partial count of HITS measured in the MCAs at different time-points during CPB. Previous studies have found no differences in the rate of retinal emboli detected by fluorescein angiography (9) or in the counts of emboli trapped in brain and lungs (10,11) between heparin-coated and standard CPB circuits during CPB. Our findings suggest that improving the biocompatibility of CPB circuits may not necessarily decrease cerebral microemboli during CPB.…”
Section: Discussionmentioning
confidence: 90%
“…In this study, we did not find any differences between SMA and standard CPB circuits in the total or partial count of HITS measured in the MCAs at different time-points during CPB. Previous studies have found no differences in the rate of retinal emboli detected by fluorescein angiography (9) or in the counts of emboli trapped in brain and lungs (10,11) between heparin-coated and standard CPB circuits during CPB. Our findings suggest that improving the biocompatibility of CPB circuits may not necessarily decrease cerebral microemboli during CPB.…”
Section: Discussionmentioning
confidence: 90%
“…Although the pulmonary marginal neutrophil reserve is excluded from the circulation during ECC, demargination of neutrophils from other organ-specific vascular beds can contribute to expansion of the circulating neutrophil pool. Because ECC is associated with limited demargination (15,16), it is likely that contributions from the marginal neutrophil pool are not likely to significantly confound our conclusions.…”
Section: Discussionmentioning
confidence: 97%
“…We anticipated that such an acute reduction in transit time may be quantifiable by determining the previously unknown rate of change in postmitotic maturation time during active neutrophil recruitment. Neutrophil postmitotic transit time was evaluated in terms of mean cellular age by modeling circulating neutrophil numbers during ECC, a stimulus that induces bone marrow neutrophil recruitment (38,41) in association with limited demargination (15,16) and which permits repeated and frequent sampling. Our model predicts the rate of change in the average age at which neutrophils exit the bone marrow during active neutrophil recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…Dogs have been used to study fluorescently labeled rehydratedlyophilized platelet incorporation into wounds by fluorescent microscopy [82], and the use of porcine platelets has been proposed for studies of cold-induced activation of platelets [83]. However, few in vivo platelet studies are reported in pigs [84,85]. Murine transfusion models have been used to dissect platelet clearance mechanisms [17,56].…”
Section: Room Temperature Versus Refrigerated Storagementioning
confidence: 99%